EXPLORING THE COMPLEXITIES OF SIVAKASI'S FIREWORKS INDUSTRY: SHADOWS OF CONCERN, SPARKS OF JOY (International Journal of Food and Nutritional Sciences, 2022)
Firework workers' hands create sparks of delight, composing the symphony of celebration. But underneath the glittering spectacles and vibrant explosions is a complicated sector full of risks and difficulties. It takes a lot of effort and talent from committed workers to make the crackers that make everyone happy. The unsung heroes of celebration, fireworks workers illuminate the night with their hard labor. In Sivakasi, India, the fireworks sector makes a substantial economic contribution to the community. Fireworks manufacture, however, raises questions over worker safety and environmental effects. This study intends to investigate the legal structure that oversees India's fireworks sector, with a particular emphasis on Sivakasi. The main laws that set standards for environmental and worker safety will be reviewed in this article. The implementation of policies and initiatives that forbid child labor as well as guaranteeing adherence to safety and environmental standards will also be covered in the report. We'll also talk about how these rules are changing and how government organizations may encourage public participation and safety awareness. This study paper aims to give a thorough overview of the regulatory environment around the Sivakasi fireworks sector by illuminating these factors.